Modified Linggui Zhugan Decoction protects against ventricular remodeling through ameliorating mitochondrial damage in post-myocardial infarction rats - Xiang, Mi; Zhao, Xin; Lu, Yingdong; Zhang, Yang; Ding, Fan; Lv, Lifei; Wang, Yuling; Shen, Zihuan; Li, Li; Cui, Xiangning (Frontiers in Cardiovascular Medicine, 2023)
Modified Linggui Zhugan Decoction (MLZD) is a Traditional Chinese Medicine prescription developed from Linggui Zhugan Decoction (LZD) that has been used for the clinical treatment of ischemic cardiovascular diseases. However, the cardioprotective mechanism of MLZD against post-myocardial infarction (MI) ventricular remodeling remains unclear. We explored the effects of MLZD on ventricular remodeling, and their underlying mechanisms, in SD rats with MI models established through left anterior descending coronary artery (LAD) ligation. MLZD treatment significantly ameliorated cardiac structure, function, and fibrosis, and thus reversed ventricular remodeling, compared with the control. Further research showed that MLZD protected against mitochondrial oxidative damage, ameliorated mitochondrial structural disruption, promoted mitochondrial fusion, prevented mitochondrial fission, restored reduced mitochondrial membrane potential, and thus inhibited apoptosis. Moreover, the decreased expression level of Sirtuin 3(SIRT3) was obviously enhanced after MLZD treatment. These findings together reveal that MLZD can apparently improve ventricular remodeling of LAD-induced MI rats through ameliorating mitochondrial damage and its associated apoptosis, which might exert protective effects by targeting SIRT3.